2007
DOI: 10.1111/j.1745-7254.2007.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is involved in cytotoxic effects of crotoxin in human breast cancer cell line MCF-7 cells

Abstract: Aim: To investigate the role of crotoxin (CrTX)‐induced autophagy in the death of MCF‐7 cells, a caspase‐3‐deficient, human breast cancer cell line. Methods: Cultured MCF‐7 cells were treated with various doses of CrTX, a phospholipase A2 (PLA2) isolated from the venom of the South American rattlesnake, Crotalus durissus terrificus. The cytotoxicity of CrTX in the presence and absence of caspase inhibitors was measured with methyl thiazolyl tetrazolium (MTT) and lactate dehydrogenase (LDH) leakage assays. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
49
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 35 publications
(44 reference statements)
5
49
0
7
Order By: Relevance
“…Previous studies have suggested that CrTX induces autophagy in human breast cancer MCF7 cells as a main mechanism for CrTX-induced cytotoxic effects [16] . In this study, we determined that CrTX induced cell apoptosis and cell cycle arrest in lung cancer A549 cells, suggesting distinct mechanisms for various types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that CrTX induces autophagy in human breast cancer MCF7 cells as a main mechanism for CrTX-induced cytotoxic effects [16] . In this study, we determined that CrTX induced cell apoptosis and cell cycle arrest in lung cancer A549 cells, suggesting distinct mechanisms for various types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, there is evidence that autophagy and apoptosis are not mutually exclusive. [24][25][26] Whether stress conditions will lead the cell to autophagy or apoptosis depends on the nature, intensity and duration of the effect, as well as the cell type and energy condition of the cell at the time that it received the effect. 27 Furthermore, although azithromycin displayed a dose-response effect on rabbit tracheal SMC proliferation, in concentrations 10 À6 -10 À5 M, 9 such a dose-dependent effect could not be observed on human bronchial SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Mizushima et al confirmed that over-expression of a fusion protein between green fluorescent protein and light chain 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 and in other cases induces apoptosis or type-2 programmed cell death [6][7][8]. Chronic myocardial ischemia/reperfusion injury induces autophagy increment and apoptosis decrement [9].…”
mentioning
confidence: 99%